Analysis of Burnout and Psychosocial Factors in Grassroot Football Referees - Orviz-Martínez, Natalia (Int J Environ Res Public Health, 2021)
The aim of this paper is to analyze the interrelationships between the burnout and different psychosocial variables to which the grassroots football referee is exposed, in particular, associated with the influence of the environment and the level of verbal and physical aggression. To this end, a questionnaire was developed, consisting of items from the Maslach Burnout Inventory-General Survey (MBI-GS) and various self-constructed items designed to find out these psychosocial variables. First, a study of the structure of the form was carried out. Second, a structural equation model was designed in order to test the causal relationship between the variables under consideration. The results obtained point to the validity of the proposed theoretical model. It is recommended to initiate training programs for this group aimed at strengthening personal coping and social support strategies, which can help minimize the evolution of this syndrome.